QoE-Driven D2D Media Services Distribution Scheme in Cellular Networks. (19th July 2017) - Chen, Mingkai; Wang, Lei; Chen, Jianxin; Wei, Xin
Abstract : Device-to-device (D2D) communication has been widely studied to improve network performance and considered as a potential technological component for the next generation communication. Considering the diverse users' demand, Quality of Experience (QoE) is recognized as a new degree of user's satisfaction for media service transmissions in the wireless communication. Furthermore, we aim at promoting user's Mean of Score (MOS) value to quantify and analyze user's QoE in the dynamic cellular networks. In this paper, we explore the heterogeneous media service distribution in D2D communications underlaying cellular networks to improve the total users' QoE. We propose a novel media service scheme based on different QoE models that jointly solve the massive media content dissemination issue for cellular networks. Moreover, we also investigate the so-called Media Service Adaptive Update Scheme (MSAUS) framework to maximize users' QoE satisfaction and we derive the popularity and priority function of different media service QoE expression. Then, we further design Media Service Resource Allocation (MSRA) algorithm to schedule limited cellular networks resource, which is based on the popularity function to optimize the total users' QoE satisfaction and avoid D2D interference. In addition, numerical simulation results indicate that the proposed scheme is more effective in cellular network content delivery, which makes it suitable for various media service propagation.